Fine Bubbles Utilization to Increase Germination Rate of Oil Palm (Elaeis guineensis L. Jacq) Seeds - Mohamad Arif; Satriyas Ilyas; Eny Widajati; Abdul Qadir; Edy Suprianto; Endah Retno Palupi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
The current method to break oil palm seed dormancy is the dry heat method which requires approximately 90 days for seeds to germinate with an average germination percentage. Therefore, hastening the process with a higher ratio of germinated seeds becomes necessary. This experiment aims to hasten and increase germination percentage by applying fine bubble water during the dormancy-breaking process. A seed lot derived from one bunch as replication is divided into two sets where fiber plugs from one of the sets are removed while the other set remains intact. Each set was re-divided into six experimental units soaked with tap water or fine bubble water for 1 to 3 days. The result showed that applying fine bubble water provided a better germination rate than tap water treatments. However, the total germination percentage between all treatments does not differ significantly. The germination peak of oil palm seed in the fine bubble water treatments occurred on the 26th day, 8 days faster than in the tap water treatments. The occurrence showed the potential use of fine bubble water application during dormancy breaking using the dry heat method.